Life table of Chrysoperla externa (Neuroptera: Chrysopidae) reared on Melanaphis sacchari (Hemiptera: Aphididae). (2020)
Chrysoperla externa is a widely distributed and highly adaptable predatory insect. In order to evaluate its capacity as a natural enemy of the sugarcane aphid, Melanaphis sacchari, its life table when reared on M. sacchari was inferred. The biological cycle lasted an average of 29.5 ± 6.2 d from egg to adult. The embryonic and larval period duration was 5.1 ± 0.3 and 13.8 ± 4.5 d, respectively. The pupa stage was completed in 10.6 ± 1.4 d, whereas adults lived 63.5 ± 26.7 d after eclosion. The mortality rate showed the highest values in the egg stage (qx = 0.17). The greatest survival rate appeared in the third instar (93.7 %). The period prior to reproduction was 6.5 ± 3.1 d. The average fecundity was 228.3 ± 139.1 eggs. The life table parameters were Ro = 113.2, T = 28.9, rm = 0.163 and λ = 1.17. According to the results, it is possible to infer that C. externa is capable of accomplishing its life cycle feeding only on M. sacchari.